Proposed Marketing Strategies For Traditional Songket Businesses: Preserving Cultural Heritage In The Modern Fashion Era - Dita, Olivi Onma; Dalimunthe, Gallang Perdhana (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The global fashion industry has undergone significant transformation driven by shifting consumer values toward authenticity, sustainability, and cultural meaning. This study analyzes the strategic challenges faced by Olivi Songket, a traditional Bataknese Songket fashion business experiencing a 30–40% decline in sales from 2024 to 2025 despite growing global demand for cultural and ethical fashion. Drawing from qualitative methods including interviews, consumer surveys, and secondary data, this research applies the Fishbone Diagram, Porter’s Five Forces, VRIO, TOWS Matrix, and Marketing Mix (7Ts) to identify root causes and formulate an actionable marketing strategy. Findings indicate that weak digital visibility, limited product variation, inconsistent communication, and rising fast-fashion competition significantly contribute to declining performance. However, Olivi Songket possesses strong cultural craftsmanship, artisan networks, and brand authenticity that can serve as sustainable competitive advantages. The study proposes a strategic marketing plan focusing on digital storytelling, modern product design, differentiated branding, accessible pricing structures, and strengthened distribution both offline and online. By integrating cultural heritage with modern fashion expectations, the proposed strategy aims to improve market relevance while ensuring long-term cultural preservation. The results highlight how traditional fashion brands can adapt to contemporary market dynamics while maintaining artisanal integrity